A single 2000-meter exercise test to assess exercise adaptation in elite rowers during the preparatory phase - Kaczmarczyk, S.; Kasperska, A.; Dziewiecka, H.; Ostapiuk-Karolczuk, J.; Cichon-Wozniak, J.; Basta, P.; Skarpanska-Stejnborn, A. (Frontiers in Physiology, 2025)
Introduction: A 2000-m exercise test on a rowing ergometer is intended to determine the training program`s effectiveness and the proper training intensity. However, anecdotal data from rowers confirm that this test involves extremely high levels of exercise, which may induce metabolic stress. Therefore, this observational study aims to analyze the effects of a 2000-m exercise test on biomarkers of inflammation, oxidative stress, and the immune system during the preparation phase in elite rowers.